Impact of Corporate Governance on Accounting Conservatism and Company Performance - Mustafa, Firas Mahmood; AL-Kanani, Muhamad Falih Hassan; Subhe, Adel; Hassan, Nazar Flayih (Journal of Ecohumanism, 2024)
Background: The financial reporting and performance of a company are greatly impacted by corporate governance. Accounting conservatism, which involves promptly acknowledging possible losses and delaying the recognition of profits, plays a crucial role in this evolving scenario. Having strong corporate governance can improve accounting conservatism, which in turn influences the overall performance of the company. Objective: The article intends to investigate how corporate governance influences accounting conservatism and assess the resulting impact on company performance. Methods: The study utilizes a quantitative methodology, examining information from a decade-long span (2010-2020) of 150 companies that are listed on the stock market. Important measures of corporate governance like board independence, CEO duality, and audit committee effectiveness were analyzed along with accounting conservatism and key performance indicators such as return on assets (ROA) and earnings per share (EPS). Results: The analysis shows a direct correlation between effective corporate governance and accounting conservatism. Companies that have a greater level of independence on their board of directors showed a 15% increase in their conservatism index when compared to companies with lower board independence. Moreover, companies that utilized more stringent accounting practices experienced a 10% rise in Return on Assets (ROA) and an 8% enhancement in Earnings Per Share (EPS) throughout the research duration. Conclusion: The results indicate that strong corporate governance improves accounting conservatism, leading to a positive impact on company performance. These findings highlight the significance of utilizing successful governance measures to guarantee financial stability and increased shareholder value.